Quantitative multivoxel proton MR spectroscopy for the identification of white matter abnormalities in mild traumatic brain injury: Comparison between regional and global analysis. Issue 5 (13th March 2019) - Davitz, Matthew S.; Gonen, Oded; Tal, Assaf; Babb, James S.; Lui, Yvonne W.; Kirov, Ivan I.
Abstract : Background: 3D brain proton MR spectroscopic imaging ( 1 H MRSI) facilitates simultaneous metabolic profiling of multiple loci, at higher, sub‐1 cm 3, spatial resolution than single‐voxel 1 H MRS with the ability to separate tissue‐type partial volume contribution(s). Purpose: To determine if: 1) white matter (WM) damage in mild traumatic brain injury (mTBI) is homogeneously diffuse, or if specific regions are more affected; 2) partial‐volume‐corrected, structure‐specific 1 H MRSI voxel averaging is sensitive to regional WM metabolic abnormalities. Study Type: Retrospective cross‐sectional cohort study. Population: Twenty‐seven subjects: 15 symptomatic mTBI patients, 12 matched controls. Field Strength/Sequence: 3T using 3D 1 H MRSI over a 360‐cm 3 volume of interest (VOI) centered over the corpus callosum, partitioned into 480 voxels, each 0.75 cm 3 . Assessment: N ‐acetyl‐aspartate (NAA), creatine, choline, and myo ‐inositol concentrations estimated in predominantly WM regions: body, genu, and splenium of the corpus callosum, corona radiata, frontal, and occipital WM. Statistical Tests: Analysis of covariance (ANCOVA) to compare patients with controls in terms of regional concentrations. The effect sizes (Cohen's d ) of the mean differences were compared across regions and with previously published global data obtained with linear regression of the WM over the entire VOI in the same dataset. Results: Despite patients' global VOI WM NAA being significantly lower than the controls', no regional differences were observed for any metabolite. Regional NAA comparisons, however, were all unidirectional (patients' NAA concentrations < controls') within a narrow range: 0.3 ≤ Cohen's d ≤ 0.6. Data Conclusion: Since the patient group was symptomatic and exhibiting global WM NAA deficits, these findings suggest: 1) diffuse axonal mTBI damage; that is 2) below the 1 H MRSI detection threshold in small regions. Therefore, larger, ie, more sensitive, single‐voxel 1 H MRS, placed anywhere in WM regions, may be well suited for mTBI 1 H MRS studies, given that these results are confirmed in other cohorts. Level of Evidence: 2 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2019;50:1424–1432.